SCIENTIFIC-THEORETICAL FOUNDATIONS OF THE DEVELOPMENT OF CREATIVE THINKING IN TEENAGERS - Nigora, Ummatkulova (Journal of Higher Education and Academic Advancement, 2024)
This article talks about the changes in the psyche of teenagers, their cognitive processes and the concept of thinking, how the specific features of thinking occur during adolescence.